Benefits and risks of unilateral and bilateral ventral intermediate nucleus deep brain stimulation for axial essential tremor symptoms. (March 2019) - Mitchell, Kyle T.; Larson, Paul; Starr, Philip A.; Okun, Michael S.; Wharen, Robert E.; Uitti, Ryan J.; Guthrie, Barton L.; Peichel, DeLea; Pahwa, Rajesh; Walker, Harrison C.; Foote, Kelly; Marshall, Frederick J.; et al.
Abstract: Introduction: Many experts assume bilateral deep brain stimulation (DBS) is necessary to improve axial tremor in essential tremor (ET). In the largest clinical trial of DBS for ET to date evaluating a non-directional, constant current device, we studied the effects of unilateral and staged bilateral DBS on axial tremor. Methods: We included all participants from the original trial with unilateral ventral intermediate nucleus (VIM) DBS and 90-day follow up at minimum. Primary outcomes were changes in pooled axial subscores in the Clinical Rating Scale for Tremor (CRST) at 90 and 180 days after activation of unilateral VIM DBS compared to pre-operative baseline (n=119). Additionally, we performed within-subject analyses for unilateral versus bilateral DBS at 180 days in the cohort who underwent staged surgery to bilateral DBS (n=39). Results: Unilateral VIM DBS improved midline tremor by 58% at 90 days (median[IQR]) (3[3] to 1[2], p<0.001) and 65% at 180 days (3[3] to 1[2], p<0.001) versus pre-op baseline. In the staged to bilateral DBS cohort, midline tremor scores further improved after bilateral DBS at 180 days by 63% versus unilateral DBS (3[3] to 1[3], p=0.007). There were, however, 35 additional DBS and surgery-related adverse events, 14 related to incoordination, gait impairment, or speech impairment, versus 6 after unilateral DBS. Conclusion: Unilateral VIM DBS for ET significantly improved associated axial tremor. Staged bilateral DBS was associated with additional axial tremor improvement but also additional adverse events. Unilateral VIM DBS may be sufficient to achieve a goal of contralateral limb and axial tremor attenuation. Highlights: Unilateral thalamic stimulation significantly improves axial essential tremor. Bilateral deep brain stimulation provides additional head tremor benefit. More adverse events occur after second lead placement in staged surgery. Predictive factors for improvement after unilateral surgery were not found.